2022
DOI: 10.1186/s12991-022-00391-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotional blunting in patients with depression. Part IV: differences between patient and physician perceptions

Abstract: Background Emotional blunting is common in patients with depression. An online survey was undertaken to assess the experience of emotional blunting, and its impact on functioning and quality of life, in the acute and remission phases of depression from the perspective of patients and healthcare providers (HCPs). This paper presents data on the level of concordance between patient and HCP perspectives. Methods This was a cross-sectional, observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This lack of acknowledgment remains a significant barrier to recovery. Studies have shown that healthcare professionals may also underestimate the prevalence, severity, and impact of EB on patient functioning and treatment adherence when compared with the patients' own perspectives 14 . Interestingly, about half of the patients with EB in our study reported that they would like their physician to ask about their EB symptoms, and nearly two‐thirds of the patients with EB symptoms found them distressing and likely to negatively impact recovery.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This lack of acknowledgment remains a significant barrier to recovery. Studies have shown that healthcare professionals may also underestimate the prevalence, severity, and impact of EB on patient functioning and treatment adherence when compared with the patients' own perspectives 14 . Interestingly, about half of the patients with EB in our study reported that they would like their physician to ask about their EB symptoms, and nearly two‐thirds of the patients with EB symptoms found them distressing and likely to negatively impact recovery.…”
Section: Discussionmentioning
confidence: 64%
“…Studies have shown that healthcare professionals may also underestimate the prevalence, severity, and impact of EB on patient functioning and treatment adherence when compared with the patients' own perspectives. 14 Interestingly, about half of the patients with EB in our study reported that they would like their physician to ask about their EB symptoms, and nearly two‐thirds of the patients with EB symptoms found them distressing and likely to negatively impact recovery. Overall, this suggests that increasing awareness of EB symptoms in both patients and physicians is necessary to improve detection and reduce suffering in patients with MDD.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Emotional blunting is highly clinically relevant in depressed patients as it compromises their quality of life by reducing their ability to process social interactions, self‐reflect, and be empathic. Numbness of feelings and emotions may result in indifference toward loved ones and friends, negatively impacting interpersonal relationships and social judgments (Christensen et al., 2022). Therefore, clinical recognition and screening for emotional numbness along with other symptom domains (i.e., cognitive and somatic) of depression is imperative to achieve an increase in quality of life, social relationships, and premorbid functionality.…”
Section: Discussionmentioning
confidence: 99%